Hydrophobic monomer and preparation method thereof, polymer and preparation method and application thereof

By introducing phosphonate groups and siloxane groups of hydrophobic monomers into the coating inhibitor, the problem of insufficient inhibitory performance and weather resistance under high temperature conditions in the prior art is solved, and water sensitivity to drilling fluid is achieved Effective control of caustic clay prevents well wall instability and drill bit abnormality.

CN119161381APending Publication Date: 2024-12-20CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310736237.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing coating inhibitors have insufficient inhibitory performance and weather resistance under high temperature conditions, and cannot effectively prevent the hydration and dispersion of water-sensitive clay in the drilling fluid, resulting in instability of the well wall and abnormal drill bits.

Method used

Using a hydrophobic monomer, the polymer prepared through it is used as a coating inhibitor, and using phosphonate groups and siloxane groups to maintain the hydrophobicity and chemical adsorption of the clay surface under high temperature conditions, enhancing inhibitory performance and weather resistance sex.

Benefits of technology

It significantly improves the inhibitory performance and weather resistance of coating inhibitors under high temperature conditions, effectively prevents the hydration and dispersion of water-sensitive clay in drilling fluid, prolongs the durability of inhibitory performance, and is suitable for high-temperature formation environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161381A_ABST
    Figure CN119161381A_ABST
Patent Text Reader

Abstract

The invention relates to the field of petroleum additives, and discloses a hydrophobic monomer and a preparation method thereof, and a polymer and a preparation method and application thereof. Wherein the hydrophobic monomer has a structure shown in a formula (1): # imgabs0 #, R10 and R20 are respectively and independently selected from hydrogen or C1-C6 alkyl, R is selected from hydrogen, phenyl or C1-C6 alkyl, R10 and R20 are respectively and independently selected from hydrogen, phenyl, C1-C18 alkyl or C6-C18 cycloalkyl, and s is selected from a natural number from 0 to 9. The hydrophobic monomer provided by the invention contains a phosphonate group and is beneficial to enhancing the temperature resistance and weather resistance of the coating inhibitor, so that the coating inhibitor is suitable for a high-temperature stratum environment, and the durability of the inhibition performance can be kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petroleum additives, and in particular to a hydrophobic monomer and a preparation method thereof, a polymer and a preparation method and application thereof. Background Art

[0002] In drilling projects, when drilling in shale formations with water-based drilling fluid, the water-sensitive clay minerals in the shale have a strong hydration and dispersion effect, which often leads to shrinkage and collapse of the wellbore wall instability, which in turn causes drilling complications and even drill stuck accidents. The rock cuttings that enter the drilling fluid are dispersed into small particles under the hydration effect, which will directly cause the viscosity of the drilling fluid to soar. In severe cases, it will cause abnormal conditions such as mud-packing of the drill bit, abnormal pump pressure, and difficulty in starting the pump. Adding inhibitors to the drilling fluid can effectively alleviate or eliminate the accident risks caused by the hydration of water-sensitive clay minerals.

[0003] Inhibitors usually work in two ways: one is to attach to the surface of the rock and form a hydrophobic film on the surface of the rock, thereby preventing water in the drilling fluid from penetrating into the rock, that is, to inhibit the hydration of water-sensitive rocks by increasing the migration resistance of water molecules in the drilling fluid. Commonly used coated inhibitors, such as potassium polyacrylamide (KPAM), zwitterionic polymer coating agents (FA-367) and many cationic polymers, belong to this type of inhibitors; the other is to enter the clay crystal layer and adsorb to the inner surface of the clay crystal layer under the action of hydrogen bonds, electrostatic attraction or van der Waals forces, thereby binding the clay layers together and squeezing out some of the interlayer adsorbed water, thereby weakening the hydration dispersion of the clay. At present, the polyamine inhibitors used on site are typical inhibitors of this type (intercalation inhibitors). In field construction, when entering the shale well section, coated inhibitors are often the preferred inhibitors. However, for the coated inhibitors currently used, the adsorption performance and temperature resistance of the inhibitors are often emphasized, but the salt and calcium resistance of this type of inhibitors are not considered.

[0004] CN109971438B discloses a modified starch anti-collapse agent. The agent is a starch glucose structural unit in which a hydrophobic group is introduced, which achieves the purpose of preventing water molecules in the drilling fluid from entering the water-sensitive clay mineral interlayer, and the temperature resistance can reach 120°C. It can be seen that the introduction of hydrophobic groups into a polymer with strong adsorption plays a positive role in improving the coating inhibition of the polymer. However, as far as the coating inhibitors that have been released so far are concerned, there are few products with a temperature resistance exceeding 120°C. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of poor inhibition performance, weather resistance, adsorption capacity and temperature resistance of the coated inhibitor in the prior art, and to provide a hydrophobic monomer and a preparation method thereof, a polymer and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides a hydrophobic monomer in a first aspect, wherein the hydrophobic monomer has a structure shown in formula (1):

[0007] Among them, R 10 and R 20 Each is independently selected from hydrogen or C1-C6 alkyl, R is selected from hydrogen, phenyl or C1-C6 alkyl, R 10 and R 20 Each independently selected from hydrogen, phenyl, C1-C 18 Alkyl or C6-C 18 Cycloalkyl, s is selected from a natural number of 0-9.

[0008] The second aspect of the present invention provides a method for preparing a hydrophobic monomer, wherein the preparation method comprises: in the presence of a catalyst, subjecting a compound a represented by formula (2) and a compound b represented by formula (3) to a synthesis reaction to obtain the hydrophobic monomer,

[0009] Among them, R 10 , R 20 ,R,s,R 10 , R 20 The same as the definition in any one of claims 1 to 3.

[0010] The third aspect of the present invention provides a hydrophobic monomer prepared by the preparation method of the second aspect of the present invention.

[0011] A fourth aspect of the present invention provides a polymer, wherein the polymer contains a structural unit A derived from a monomer a represented by formula (4), a structural unit B derived from a monomer b represented by formula (5), a structural unit C and a structural unit D derived from a monomer c represented by formula (6);

[0012]

[0013] Wherein, the structural unit D is derived from the hydrophobic monomers described in the first and third aspects of the present invention;

[0014] Among them, in formula (4), R 1 is selected from hydrogen or C1-C6 alkyl,

[0015] R 2 Selected from in,

[0016] R a and R b Each is independently selected from hydrogen, C1-C6 alkyl, C1-C6 alkyl alcohol or C1-C8 alkyl ketone,

[0017] R c is selected from hydrogen or C1-C6 alkyl,

[0018] R d is selected from methyl, ethyl or isopropyl;

[0019] Among them, in formula (5), R 3 is selected from hydrogen or C1-C6 alkyl,

[0020] R 4 Selected from

[0021] wherein j, k, and l are each independently selected from natural numbers of 0 to 3, m and n are each independently selected from integers of 4 to 14, and A is selected from H, Na, K, Rb or Cs, preferably selected from H, Na or K;

[0022] Among them, in formula (6), R 5 is selected from hydrogen or C1-C6 alkyl,

[0023] R 6 is a siloxane group selected from wherein p and q are each independently selected from a natural number of 0-6, preferably a natural number of 0-3, more preferably 1, 2 and 3,

[0024] R a , R b , R c , R d , R e and R f Each is independently selected from an alkyl group or an -OR' group, wherein the alkyl group is selected from a methyl group, R' is selected from a methyl group, an ethyl group, -CH2CH2OCH3 or -CH2CH2OCH2CH2OCH3, and R a , R b and R c Not all methyl groups, R d , R e and R f At least one of them is an alkoxy group.

[0025] The fifth aspect of the present invention provides a method for preparing a polymer, wherein the method comprises: in the presence of an initiator, polymerizing monomer a, monomer b, monomer c and the hydrophobic monomer described in the first and third aspects of the present invention to obtain the polymer.

[0026] The sixth aspect of the present invention provides a polymer obtained by the preparation method of the fifth aspect of the present invention.

[0027] The seventh aspect of the present invention provides a use of the polymers described in the third and sixth aspects of the present invention as coated inhibitors in drilling fluids.

[0028] Through the above technical scheme, the hydrophobic monomer of the present invention has a phosphonate group, and the polymer prepared by using the hydrophobic monomer is a hydrophobic associating polymer, which is used for water-based drilling fluid coating inhibitors and has good inhibition and temperature resistance. First, after the coating inhibitor is adsorbed with clay, due to the presence of hydrophobic groups in the molecular chain, the clay surface maintains a certain hydrophobicity, slowing down the tendency of water in the drilling fluid liquid phase to invade the interlayer of the clay lamellar structure, and reducing the hydration of the clay. Second, siloxane groups are introduced into the molecular chain of the coating inhibitor, which is hydrolyzed in the water phase to generate Si-OH, and reacts with Si-OH on the clay surface and end face under alkaline conditions to generate Si-O-Si, thereby realizing chemical adsorption between the coating inhibitor and the clay. This adsorption is less affected by temperature, and can effectively reduce the desorption of the coating inhibitor under high temperature conditions, thereby improving the effect of the coating inhibitor under high temperature conditions. Thirdly, the hydrophobic monomer provided by the present invention contains a phosphonate group, which is beneficial to enhancing the temperature resistance and weather resistance of the coated inhibitor, thereby making the coated inhibitor suitable for high-temperature formation environments and being able to maintain the durability of the inhibitory performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is the magnetic resonance spectrum of Preparation Example 1;

[0030] Figure 2 is the magnetic resonance spectrum of Preparation Example 2;

[0031] Figure 3 is the magnetic resonance spectrum of Preparation Example 3;

[0032] Figure 4 is the magnetic resonance spectrum of Preparation Example 4. DETAILED DESCRIPTION

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] The first aspect of the present invention provides a hydrophobic monomer, wherein the hydrophobic monomer has a structure shown in formula (1):

[0035] Among them, R 10 and R20 Each is independently selected from hydrogen or C1-C6 alkyl, R is selected from hydrogen, phenyl or C1-C6 alkyl, R 10 and R 20 Each independently selected from hydrogen, phenyl, C1-C 18 Alkyl or C6-C 18 Cycloalkyl, s is selected from a natural number of 0-9.

[0036] In some specific embodiments of the present invention, wherein R 10 and R 20 Each is independently selected from C1-C4 alkyl, preferably methyl, ethyl, isopropyl or isobutyl.

[0037] In some specific embodiments of the present invention, R is selected from phenyl or C1-C6 straight-chain alkyl, preferably selected from methyl, ethyl, n-butyl, n-hexyl or phenyl.

[0038] In some specific embodiments of the present invention, R 10 and R 20 Each independently selected from hydrogen, phenyl, C1-C 18 The straight-chain alkyl group is preferably selected from hydrogen, methyl, n-propyl, n-pentyl, phenyl, n-decyl or n-heptadecayl.

[0039] In some specific embodiments of the present invention, s is selected from a natural number of 0-6, preferably selected from 1, 2 or 3.

[0040] In the present invention, the hydrophobic monomer of the present invention has a phosphonate group, and the polymer prepared by using the hydrophobic monomer is a hydrophobic associating polymer. After the coated inhibitor is adsorbed on the clay, due to the presence of the hydrophobic group in the molecular chain, the clay surface maintains a certain hydrophobicity, which slows down the tendency of water in the drilling fluid liquid phase to invade the interlayers of the clay lamellar structure, reduces the hydration of the clay, and is beneficial to enhancing the temperature resistance and weather resistance of the coated inhibitor, so that the coated inhibitor is suitable for high-temperature formation environment and can maintain the durability of the inhibitory performance.

[0041] In some specific embodiments of the present invention, the hydrophobic monomer is selected from the compounds represented by the following structural formula:

[0042]

[0043]

[0044]

[0045] The second aspect of the present invention provides a method for preparing a hydrophobic monomer, wherein the preparation method comprises: in the presence of a catalyst, subjecting a compound a represented by formula (2) and a compound b represented by formula (3) to a synthesis reaction to obtain the hydrophobic monomer,

[0046] Among them, R 10 , R 20 ,R,s,R 10 , R 20 The definitions correspond to those described above.

[0047] In some specific embodiments of the present invention, the catalyst is selected from at least one of low-valent titanium, low-valent tungsten, low-valent molybdenum, low-valent zirconium, low-valent vanadium and low-valent niobium; preferably low-valent titanium.

[0048] In some specific embodiments of the present invention, the method for preparing low-valent titanium comprises: dissolving a titanium-containing reagent and a reducing agent in a first solvent, and performing a reduction reaction to obtain the low-valent titanium.

[0049] In some specific embodiments of the present invention, the method for preparing low-valent titanium also includes: the reduction reaction is carried out under a protective atmosphere, wherein the protective atmosphere is nitrogen and / or argon; when the protective atmosphere is a mixed gas of nitrogen and argon, nitrogen and argon can be mixed in any proportion.

[0050] In some specific embodiments of the present invention, the first solvent is selected from tetrahydrofuran and / or dimethyl ether.

[0051] In some specific embodiments of the present invention, the titanium-containing reagent is selected from at least one of titanium trichloride, titanium tetrachloride and titanium powder; the reducing agent is selected from at least one of K, Li, Na, Zn+CuCl, LiAlH4, Mg, Mg+Hg, Li+Hg and chlorosilane; when the reducing agents are selected in multiple ways, the proportion relationship is not limited, and the valence state of low-valent titanium generally varies with the reduction activity of the reducing agent and the molar ratio of the reducing agent to titanium trichloride, titanium tetrachloride and commercial titanium powder.

[0052] In some specific embodiments of the present invention, preferably, the titanium-containing reagent is titanium tetrachloride; and the reducing agent is Zn and CuCl.

[0053] In some specific embodiments of the present invention, the concentration of titanium tetrachloride in the first solvent is 0.3-0.6 mmol / mL, the concentration of Zn in the first solvent is 0.2-0.6 mmol / mL, and the concentration of CuCl in the first solvent is 0.03-0.05 mmol / mL.

[0054] In some specific embodiments of the present invention, the method for preparing low-valent titanium further specifically includes: adding activated Zn, CuCl and solvent A to a reactor in the presence of a protective gas, then cooling and stirring, and then adding TiCl4 to perform the reduction reaction in a reflux manner to obtain low-valent titanium.

[0055] According to a preferred embodiment of the present invention, when the solvent A is THF, the reflux temperature is 68-75°C, and cooling is required after reflux; when the solvent A is DME, the reflux does not need to be heated or cooled again.

[0056] Preferably, the particle size of the activated Zn is above 200 mesh, more preferably 200-600 mesh.

[0057] Preferably, the cooling temperature is -10 to 0°C, and the reflux time is 2-8h, preferably 3-6h.

[0058] In some specific embodiments of the present invention, before the reaction of compound a and compound b, compound a and compound b are dissolved in a second solvent, wherein the volume ratio of the first solvent to the second solvent is 2-4:1.

[0059] In some specific embodiments of the present invention, the molar ratio of compound a to compound b is 1:1.2-1.8.

[0060] In some specific embodiments of the present invention, the method for preparing the hydrophobic monomer comprises: dissolving the compound a and the compound b in a second solvent, mixing them into a low-valent titanium reagent, and performing the synthesis reaction in a reflux manner under stirring conditions.

[0061] In some specific embodiments of the present invention, the temperature of the synthesis reaction is -10°C to 0°C or 68-75°C; the reaction time is 2-8h, preferably 3-6h. Specifically, when the second solvent is THF, the temperature of the synthesis reaction is 68-75°C; when the second solvent is DME, the temperature of the synthesis reaction is -10 to 0°C.

[0062] The preparation method of the hydrophobic monomer provided by the present invention may further include a quenching reaction after the synthesis reaction proceeds to a certain extent. Because there are excess reactants in the synthesis reaction, when the reaction proceeds to a certain extent, the target product has been obtained, and if the excess reactants continue to exist, they will further react to generate undesirable products. The principle of quenching is to use another compound that is more likely to react with the excess compound to react with it, thereby removing it from the system.

[0063] In order to avoid the presence of impurities in the product, the present invention preferably performs a quenching reaction after the synthesis reaction is carried out to a certain extent, that is, after the hydrophobic monomer preparation reaction is completed. The present invention has no particular restrictions on the quenching agent, and conventional quenching agents such as alkali metal cyanide, amide, borane, K2CO3, LiAlH4 and NaBH4 can be selected. However, considering the stability of the product and the ease of handling, the present invention preferably uses K2CO3 as the quenching agent.

[0064] In some specific embodiments of the present invention, after a period of reaction, a K2CO3 solution is added to quench the reaction, the concentration of the K2CO3 is 5.0-20.0wt%, preferably 8.0-12.0wt%, and the volume ratio of the K2CO3 solution to the second solvent is 1:5-10.

[0065] In some specific embodiments of the present invention, the mixture obtained by the reaction is dried, filtered, distilled, and recrystallized to obtain the hydrophobic monomer.

[0066] The third aspect of the present invention provides a hydrophobic monomer prepared by the preparation method of the second aspect of the present invention, which may have the composition and structure of the first aspect, and will not be described in detail here.

[0067] A fourth aspect of the present invention provides a polymer, wherein the polymer contains a structural unit A derived from a monomer a represented by formula (4), a structural unit B derived from a monomer b represented by formula (5), a structural unit C and a structural unit D derived from a monomer c represented by formula (6);

[0068]

[0069] Wherein, the structural unit D is derived from the hydrophobic monomers described in the first and third aspects of the present invention;

[0070] Among them, in formula (4), R 1 is selected from hydrogen or C1-C6 alkyl,

[0071] R 2 Selected from Among them, R a and R b Each is independently selected from H, C1-C6 alkyl, C1-C6 alkyl alcohol or C1-C8 alkyl ketone, R c is selected from hydrogen or C1-C6 alkyl, R d is selected from methyl, ethyl or isopropyl;

[0072] Among them, in formula (5), R 3 is selected from hydrogen or C1-C6 alkyl,

[0073] R 4 Selected from

[0074] wherein j, k, and l are each independently selected from a natural number of 0 to 3, m and n are each independently selected from an integer of 4 to 14, and A is selected from H, Na, K, Rb or Cs, preferably selected from H, Na or K;

[0075] Among them, in formula (6), R 5 is selected from hydrogen or C1-C6 alkyl,

[0076] R 6 is a siloxane group selected from wherein p and q are each independently selected from a natural number of 0-6, preferably a natural number of 0-3, more preferably 1, 2 and 3,

[0077] R a , R b , R c , R d , R e and R f Each is independently selected from an alkyl group or an OR' group, wherein the alkyl group is selected from a methyl group, R' is selected from a methyl group, an ethyl group, -CH2CH2OCH3 or -CH2CH2OCH2CH2OCH3, and R a , R b and R c Not all methyl groups, i.e. R a , R b and R c At least one of them is an alkoxy group, R d , R e and R f At least one of them is an alkoxy group.

[0078] In some specific embodiments of the present invention, the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is (30-50): (10-25): (3-8): (1-3).

[0079] In some specific embodiments of the present invention, the weight average molecular weight of the polymer is 2.15×10 6 -3.25×10 6 g / mol.

[0080] In the present invention, siloxane groups are introduced into the polymer molecular chain, which is hydrolyzed in the aqueous phase to generate Si-OH, and undergoes a condensation reaction with Si-OH on the surface and end face of the clay under alkaline conditions to generate Si-O-Si, thereby achieving chemical adsorption between the coating inhibitor and the clay. This adsorption effect is less affected by temperature and can effectively reduce the desorption of the coating inhibitor under high temperature conditions, thereby improving the effect of the coating inhibitor under high temperature conditions.

[0081] In the present invention, the structural unit a from the alkenyl amide monomer is introduced into the polymer molecular chain to provide the polymer with an adsorption group, so that the polymer has better solubility. The structural unit b from the alkenyl sulfonic acid monomer is introduced into the polymer molecular chain to provide the polymer with a hydration group, which also improves the polymer's resistance to temperature and salt. Therefore, in the present invention, four monomers are introduced into the polymer to jointly constitute the structural unit of the polymer, so that when the polymer is used for coating the inhibitor of the water-based drilling fluid, it has good inhibition and temperature resistance.

[0082] In some specific embodiments of the present invention, the polymer comprises at least one of the following polymers:

[0083] Polymer-1, the structural unit A is derived from acrylamide, the structural unit B is derived from sodium p-styrene sulfonate, the structural unit C is derived from γ-methacryloxypropyltrimethoxysilane, the structural unit D is derived from a compound of formula (1-1), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.4:0.15:0.04:0.02,

[0084]

[0085] Polymer-2, the structural unit A is derived from diacetone acrylamide, the structural unit B is derived from sodium p-allyl sulfonate, the structural unit C is derived from N-(3-triethoxysilyl)propyl acrylamide, the structural unit D is derived from the compound of formula (1-1), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.3:0.25:0.08:0.03,

[0086]

[0087] Polymer-3, the structural unit A is derived from N-vinyl acetamide, the structural unit B is derived from sodium 2-acryloyloxyhexadecyl sulfonate, the structural unit C is derived from (methacryloyloxymethyl)methyldimethoxysilane, and the structural unit D is derived from a compound of formula (1-1), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.5:0.1:0.03:0.01,

[0088]

[0089] Polymer-4, the structural unit A is derived from N-ethylacrylamide, the structural unit B is derived from 3-prop-2-enoyloxypropane-1-sulfonic acid, the structural unit C is derived from (methacryloxypropyl) dimethylethoxyethoxymethoxysilane, the structural unit D is derived from the compound of formula (1-1), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.35:0.2:0.06:0.02,

[0090]

[0091] Polymer-5, the structural unit A is derived from N,N-bis(2-hydroxyethyl)methacrylamide, the structural unit B is derived from 2-acrylamide-2-methylpropanesulfonic acid, the structural unit C is derived from (methacryloxypropyl)triethoxymethoxysilane, the structural unit D is derived from the compound of formula (1-2), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.5:0.1:0.08:0.03,

[0092]

[0093] Polymer-6, the structural unit A is derived from N-(2-hydroxypropyl) acrylamide, the structural unit B is derived from sodium 2-acrylamido octane sulfonate, the structural unit C is derived from (methacryloxypropyl)methyldiethoxysilane, the structural unit D is derived from the compound of formula (1-2), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.33:0.18:0.05:0.025,

[0094]

[0095] Polymer-7, the structural unit A is derived from N,N-diethyl methacrylamide, the structural unit B is derived from sodium 2-acrylamido hexadecyl sulfonate, the structural unit C is derived from (acrylamidopropyl) trimethoxysilane, the structural unit D is derived from a compound of formula (1-2), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.3:0.25:0.03:0.01,

[0096]

[0097] Polymer-8, the structural unit A is derived from N-vinyl-N-methylacetamide, the structural unit B is derived from sodium methyl propylene sulfonate, the structural unit C is derived from (methacryloxypropyl)methyldiethoxyethoxymethoxysilane, the structural unit D is derived from the compound of formula (1-2), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.36:0.17:0.07:0.02,

[0098]

[0099] Polymer-9, the structural unit A is derived from N-isopropylacrylamide, the structural unit B is derived from 3-prop-2-enamidopropane-1-sulfonate potassium, the structural unit C is derived from (acryloyloxyethyl) dimethylmethoxysilane, the structural unit D is derived from the compound of formula (1-3), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.3:0.1:0.08:0.01,

[0100]

[0101] Polymer-10, the structural unit A is derived from N-(2-hydroxypropyl) acrylamide, the structural unit B is derived from potassium 2-acrylamidodecyl sulfonate, the structural unit C is derived from (acrylamidopropyl) triethoxyethoxymethoxysilane, the structural unit D is derived from a compound of formula (1-4), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.5:0.25:0.03:0.03,

[0102]

[0103] Polymer-11, the structural unit A is derived from N-hydroxyethyl acrylamide, the structural unit B is derived from potassium 2-acrylamido-2-methylpropanesulfonate, the structural unit C is derived from γ-methacryloxypropyltrimethoxysilane, and the structural unit D is derived from a compound of formula (1-5), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.3:0.1:0.03:0.03,

[0104]

[0105] Polymer-12, the structural unit A is derived from N-hydroxymethyl acrylamide, the structural unit B is derived from sodium 2-acryloyloxy-2-methylpropane sulfonate, the structural unit C is derived from N-(3-triethoxysilyl)propyl acrylamide, the structural unit D is derived from the compound of formula (1-5), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.43:0.2:0.04:0.015,

[0106]

[0107] Polymer-13, the structural unit A is derived from N,N-diethylacrylamide, the structural unit B is derived from sodium 2-acrylamidododecylsulfonate, the structural unit C is derived from (acrylamidopropyl)trimethoxysilane, the structural unit D is derived from a compound of formula (1-6), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.35:0.15:0.04:0.02,

[0108]

[0109] Polymer-14, the structural unit A is derived from N,N-dimethylacrylamide, the structural unit B is derived from potassium 2-acrylamidododecylsulfonate, the structural unit C is derived from (methacryloxypropyl)triethoxymethoxysilane, the structural unit D is derived from a compound of formula (1-7), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.38:0.23:0.05:0.02,

[0110]

[0111] Polymer-15, the structural unit A is derived from methacrylamide, the structural unit B is derived from potassium 2-acryloyloxy-2-methylpropanesulfonate, the structural unit C is derived from (methacryloyloxypropyl)triethoxymethoxysilane, the structural unit D is derived from a compound of formula (1-7), and the molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is 0.38:0.2:0.06:0.01,

[0112]

[0113] The fifth aspect of the present invention provides a method for preparing a polymer, wherein the method comprises: in the presence of an initiator, polymerizing monomer a, monomer b, monomer c and the hydrophobic monomers described in the first and third aspects of the present invention to obtain the polymer.

[0114] In some specific embodiments of the present invention, the method follows the general rules of free radical polymerization reaction. Free radical polymerization reaction generally consists of three elementary reactions: chain initiation, chain growth, and chain termination, and may also be accompanied by chain transfer reaction.

[0115] In some specific embodiments of the present invention, the polymerization reaction is carried out in the presence of a protective gas. Preferably, the protective gas is nitrogen.

[0116] In some specific embodiments of the present invention, the following steps are specifically included:

[0117] (1) sequentially mixing monomer a, monomer b, monomer c and the hydrophobic monomer in a solvent, stirring and heating to a reaction temperature;

[0118] (2) After nitrogen is passed through for 30 minutes, an initiator is added to the mixed solution, and the reaction is continued for a period of time under stirring to obtain a crude polymer product;

[0119] (3) The crude product of the polymer is precipitated, washed, extracted and vacuum dried to obtain the polymer.

[0120] In some specific embodiments of the present invention, the solvent is selected from one or more of acetone, butanone, chloroform, dichloromethane, 1,1-dichloroethane, 1,2-dichloroethane, methyl ethyl ketone, tetrahydrofuran, petroleum ether, ether, acetonitrile, ethyl acetate, benzene, toluene, m-xylene, cyclohexane, ethylene glycol dimethyl ether, nitromethane, 1,4-dioxane, pyridine, morpholine, 4-methyl-2-pentanone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.

[0121] In some specific embodiments of the present invention, the mass percentage concentration of the four monomers in the solvent is 5-15%.

[0122] In some specific embodiments of the present invention, the initiator is one or more of an azo initiator, an organic peroxide initiator, an inorganic peroxide initiator, and an oil-soluble redox initiator, preferably an azo initiator.

[0123] In some specific embodiments of the present invention, preferably, the azo initiator is selected from one or more of azobisisobutylimidazoline hydrochloride, azoisobutylcyanoformamide, azobisisobutyronitrile, azobiscarboxyethyl-2-isobutylamidine hydrate, azodimethyl N-2-hydroxybutylacrylamide, azobiscyclohexylcarbonitrile, azobisisovaleronitrile, azobisisoheptylnitrile, azobiscyanovaleric acid, azobisisobutylamidine hydrochloride, azobisisopropylimidazoline, azobisN-hydroxyisobutylamidine hydrate, azobisN,N'-cyclobutylisobutylamidine hydrate, azobisdimethylisobutyrate, and 2,2'-azobis(N-cyclohexylisobutylamidine) hydrochloride.

[0124] In some specific embodiments of the present invention, the reaction temperature is 40-105°C, preferably 44-104°C; and the reaction time is 16-24h.

[0125] In some specific embodiments of the present invention, the molar ratio of the monomer a, monomer b, monomer c and the hydrophobic monomer is (30-50): (10-25): (3-8): (1-3).

[0126] In some specific embodiments of the present invention, the amount of the initiator added is 0.2-2 wt % of the total weight of the monomer a, monomer b, monomer c and the hydrophobic monomer.

[0127] In the present invention, the composition and structure of the polymer can be determined by NMR, IR, GPC, elemental analysis, etc., or by preparing and feeding.

[0128] The sixth aspect of the present invention provides a polymer obtained by the preparation method of the fifth aspect of the present invention.

[0129] The seventh aspect of the present invention provides a use of the polymers described in the third and sixth aspects of the present invention as coated inhibitors in drilling fluids.

[0130] The present invention will be described in detail below through examples.

[0131] In the following examples and comparative examples, if no specific conditions are specified, the experiments are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be obtained through commercial channels. The composition and structure of the hydrophobic monomers and polymers described in the following examples and comparative examples can be determined by nuclear magnetic resonance, infrared, GPC, elemental analysis, etc., or by preparing and feeding.

[0132] Preparation Example 1

[0133] Under nitrogen protection, 26.152 g (400 mmol) of 400 mesh activated Zn powder, 3.96 g (40 mmol) of CuCl and 1000 mL of DME were added into the reactor, the temperature was controlled to -10 °C, stirred, 94.8395 g (500 mmol) of TiCl4 was added, and refluxed for 4 h to obtain the catalyst.

[0134] Dissolve 21.6168g (120mmol) (2-butanone) dimethyl phosphonate and 35.2518g (200mmol) hexanophenone in 400mL of DME, mix into the catalyst, and reflux for 4h. Add 50mL of 12.0wt% K2CO3 solution, filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate to obtain a mixed solution. Add enough anhydrous Na2SO4 to the mixed solution, filter, remove DME, and obtain a pale yellow crude product.

[0135] The crude product was recrystallized from methanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 1 was characterized by NMR [(CD3)2SO, 25°C], and the magnetic resonance spectrum ( 1 H NMR) Figure 1 .according to 1 The H NMR analysis results are consistent with the molecular structure of the target product, and the molecular structure formula is as follows: That is the target hydrophobic monomer (denoted as S1) with a yield of 66.76%.

[0136] Preparation Example 2

[0137] Under argon protection, 13.076 g (200 mmol) of 600 mesh activated Zn powder, 4.95 g (50 mmol) of CuCl and 1000 mL of THF were added into the reactor, cooled to -5 °C and stirred, 56.9037 g (300 mmol) of TiCl4 was added, the temperature was raised to 68 °C and refluxed for 5 h, and then cooled to -5 °C again to obtain the catalyst.

[0138] Dissolve 14.6178g (50mmol) of diethyl heptanoylpropylphosphonate and 20.1364g (75mmol) of octadecylaldehyde in 250mL of THF, add the catalyst, heat to 68°C under stirring, and reflux for 6h. Add 25mL of 12.0wt% K2CO3 solution and filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate to obtain a mixed solution. Add enough MgSO4 to the mixed solution, filter and distill under reduced pressure to remove THF, and obtain a pale yellow crude product.

[0139] The crude product was recrystallized from methanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 2 was characterized by nuclear magnetic resonance [(CD3)2SO, 25°C]. The magnetic resonance spectrum (1H NMR) was as follows: Figure 2 According to the 1H NMR analysis results, it is consistent with the molecular structure of the target product, and the molecular structure formula is as follows:

[0140]

[0141] That is the target hydrophobic monomer (denoted as S2) with a yield of 70.16%.

[0142] Preparation Example 3

[0143] Under nitrogen protection, 39.228 g (600 mmol) of 200 mesh activated Zn powder, 2.97 g (30 mmol) of CuCl and 1000 mL of DME were added into the reactor, the temperature was controlled to 0°C, stirred, 75.8716 g (400 mmol) of TiCl4 was added, and refluxed for 5 h to obtain the catalyst.

[0144] Dissolve 26.4302g (100mmol) di-tert-butyl formylethylphosphonate and 18.510g (120mmol) 1-cyclohexane-1-butanone in 300mL of DME, mix into the catalyst, and reflux for 3h. Add 60mL of 8.0wt% K2CO3 solution, filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate to obtain a mixed solution. Add enough CaSO4 to the mixed solution, filter, and remove DME under reduced pressure to obtain a pale yellow crude product.

[0145] The crude product was recrystallized from methanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 3 was characterized by NMR [(CD3)2SO, 25°C], and the magnetic resonance spectrum ( 1 H NMR) Figure 3 .according to 1 The H NMR analysis results are consistent with the molecular structure of the target product, and the molecular structure formula is as follows:

[0146]

[0147] (denoted as S3), with a yield of 60.35%.

[0148] Preparation Example 4

[0149] Under argon protection, 32.69 g (500 mmol) of 500 mesh activated Zn powder, 3.96 g (40 mmol) of CuCl and 1000 mL of DME were added into the reactor, the temperature was controlled to -8 °C, stirred, 113.8074 g (600 mmol) of TiCl4 was added, and refluxed for 2 h to obtain the catalyst.

[0150] Dissolve 68.23g (240mmol) of diisopropyl benzoylmethylphosphonate and 31.8372g (300mmol) of benzaldehyde in 500mL of DME, mix into the catalyst, and reflux for 5h. Add 60mL of 10.0wt% K2CO3 solution, filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate, and obtain a mixed solution. Add enough CaCl2 to the mixed solution, filter, and remove DME by vacuum distillation to obtain a pale yellow crude product.

[0151] The crude product was recrystallized from ethanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 4 was characterized by NMR [(CD3)2SO, 25°C], and the magnetic resonance spectrum ( 1 H NMR) Figure 4 .according to 1 The H NMR analysis results are consistent with the molecular structure of the target product, and the molecular structure formula is as follows:

[0152] That is the target hydrophobic monomer (denoted as S4) with a yield of 62.11%.

[0153] Preparation Example 5

[0154] Under nitrogen protection, 26.152 g (400 mmol) of 500 mesh activated Zn powder, 5.95 g (50 mmol) of CuCl and 1000 mL of THF were added into the reactor, cooled to -2 °C and stirred, 91.0459 g (480 mmol) of TiCl4 was added, the temperature was raised to 75 °C and refluxed for 3 h, and then cooled to -2 °C again to obtain the catalyst.

[0155] Dissolve 16.6555g (80mmol) of dimethyl pentanoylmethylphosphonate and 11.8859g (112mmol) of benzaldehyde in 280mL of THF, add the catalyst, heat to 75°C under stirring, and reflux for 4.5h. Add 40mL of 8.0wt% K2CO3 solution and filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate to obtain a mixed solution. Add enough CaCl2 to the mixed solution, filter and distill under reduced pressure to remove THF, and obtain a pale yellow crude product.

[0156] The crude product was recrystallized from ethanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 5 was characterized by NMR [(CD3)2SO, 25°C]. 1 The H NMR analysis results are consistent with the molecular structure of the target product, and the molecular structure formula is as follows:

[0157] That is the target hydrophobic monomer (denoted as S5) with a yield of 64.72%.

[0158] Preparation Example 6

[0159] Under nitrogen protection, 29.421 g (450 mmol) of 350 mesh activated Zn powder, 4.455 g (45 mmol) of CuCl and 1000 mL of THF were added into the reactor, cooled to -4 °C and stirred, 85.3556 g (450 mmol) of TiCl4 was added, the temperature was raised to 72 °C and refluxed for 4 h, and then cooled to -4 °C again to obtain the catalyst.

[0160] Dissolve 20.8194g (100mmol) of diethyl formylmethylphosphonate and 33.1718g (180mmol) of 2-dodecanone in 360mL of THF, add the catalyst, heat to 72°C under stirring, and reflux for 6h. Add 60mL of 10.0wt% K2CO3 solution, filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate to obtain a mixed solution. Add enough anhydrous Na2SO4 to the mixed solution, filter, and remove THF under reduced pressure to obtain a pale yellow crude product.

[0161] The crude product was recrystallized from methanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 6 was characterized by NMR [(CD3)2SO, 25°C]. 1 The H NMR analysis results are consistent with the molecular structure of the target product, and the molecular structure formula is as follows:

[0162] That is the target hydrophobic monomer product (denoted as S6) with a yield of 62.17%.

[0163] Preparation Example 7

[0164] Under argon protection, 19.614 g (300 mmol) of 500 mesh activated Zn powder, 3.564 g (36 mmol) of CuCl and 1000 mL of DME were added into the reactor, the temperature was controlled to -6 °C, stirred, 113.8074 g (600 mmol) of TiCl4 was added, and refluxed for 2 h to obtain the catalyst.

[0165] Dissolve 17.7777g (80mmol) of diethyl acetylethylphosphonate and 34.7834g (112mmol) of 11-heneicosone in 320mL of DME, mix into the catalyst, and reflux for 5h. Add 40mL of 9.5wt% K2CO3 solution, filter through diatomaceous earth, collect the filtrate, rinse with CH2Cl2, mix the rinse with the filtrate to obtain a mixed solution. Add enough MgCl2 to the mixed solution, filter, and remove DME by vacuum distillation to obtain a pale yellow crude product.

[0166] The crude product was recrystallized from ethanol to obtain a light yellow powdery solid. The product obtained in Preparation Example 7 was characterized by NMR [(CD3)2SO, 25°C]. 1 The H NMR analysis results are consistent with the molecular structure of the target product, and the molecular structure formula is as follows:

[0167]

[0168] That is the target hydrophobic monomer (denoted as S7) with a yield of 66.49%.

[0169] Example 1

[0170] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 28.4316 g (0.4 mol) of acrylamide, 30.9286 g (0.15 mol) of sodium p-styrenesulfonate, 9.934 g (0.04 mol) of γ-methacryloxypropyltrimethoxysilane and 6.48 g (0.02 mol) of the hydrophobic monomer S1 prepared in Preparation Example 1 were added to 660 mL of 1,4-dioxane, mixed and stirred, and the temperature was raised to 69°C;

[0171] After nitrogen was passed through for 30 min, 0.6 g of azobiscyanovaleric acid was added to the mixed solution, and the reaction was continued for 20 h under stirring to obtain a crude product;

[0172] After adding 600 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for 3 times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P1).

[0173] The weight average molecular weight of the polymer is 2.96×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.4:0.15:0.04:0.02.

[0174] Example 2

[0175] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 50.7672 g (0.3 mol) of diacetone acrylamide, 36.03 g (0.25 mol) of sodium p-allyl sulfonate, 22.0336 g (0.08 mol) of N-(3-triethoxysilyl)propyl acrylamide and 9.72 g (0.03 mol) of the hydrophobic monomer S1 prepared in Preparation Example 1 were added to 650 mL of 1,4-dioxane, mixed and stirred, and the temperature was raised to 67°C;

[0176] After nitrogen was passed through for 30 minutes, 0.24 g of azobis(N,N'-cyclobutylisobutylamidine) hydrate was added to the mixed solution, and the reaction was continued for 24 hours under stirring to obtain a crude product;

[0177] After adding 600 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P2).

[0178] The weight average molecular weight of the polymer is 2.65×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.3:0.25:0.08:0.03.

[0179] Example 3

[0180] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 42.553 g (0.5 mol) of N-vinylacetamide, 39.8534 g (0.1 mol) of sodium 2-acryloyloxyhexadecylsulfonate, 6.1289 g (0.03 mol) (methacryloyloxymethyl)methyldimethoxysilane and 3.24 g (0.01 mol) of the hydrophobic monomer S1 obtained in Preparation Example 1 were added to 800 mL of N,N-dimethylformamide, mixed and stirred, and heated to 72°C;

[0181] After nitrogen was passed through for 30 minutes, 0.46 g of 2,2'-azobis(N-cyclohexylisobutylamidine) hydrochloride was added to the mixed solution, and the reaction was continued for 18 hours under stirring to obtain a crude product;

[0182] After adding 600 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P3).

[0183] The weight average molecular weight of the polymer is 2.76×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.5:0.1:0.03:0.01.

[0184] Example 4

[0185] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 34.6959 g (0.35 mol) of N-ethylacrylamide, 46.4592 g (0.2 mol) of 3-prop-2-enoyloxypropane-1-sulfonic acid potassium, 18.2675 g (0.06 mol) (methacryloxypropyl) dimethylethoxyethoxymethoxysilane and 6.48 g (0.02 mol) of the hydrophobic monomer S1 prepared in Preparation Example 1 were added to 2140 mL of N, N-dimethylacetamide, mixed and stirred, and the temperature was raised to 51°C;

[0186] After nitrogen was passed through for 30 min, 1.06 g of azobisisoheptanonitrile was added to the mixed solution, and the reaction was continued for 21.5 h under stirring to obtain a crude product;

[0187] After adding 1800 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P4).

[0188] The weight average molecular weight of the polymer is 3.25×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.35:0.2:0.06:0.02.

[0189] Example 5

[0190] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 86.606 g (0.5 mol) of N, N-bis (2-hydroxyethyl) methacrylamide, 20.7244 g (0.1 mol) of 2-acrylamido-2-methylpropanesulfonic acid, 30.4407 g (0.08 mol) (methacryloxypropyl) triethoxymethoxysilane and 15.8653 g (0.03 mol) of the hydrophobic monomer S2 obtained in Preparation Example 2 were added to 1600 mL of dimethyl sulfoxide, mixed and stirred, and the temperature was raised to 104° C.;

[0191] After nitrogen was passed through for 30 min, 2.78 g of azoisobutylcyanamide was added to the mixed solution, and the reaction was continued for 16 h under stirring to obtain a crude product;

[0192] After adding 1200 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P5).

[0193] The weight average molecular weight of the polymer is 2.15×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.5:0.1:0.08:0.03.

[0194] Example 6

[0195] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 42.6225 g (0.33 mol) of N-(2-hydroxypropyl) acrylamide, 51.3601 g (0.18 mol) of sodium 2-acrylamidooctane sulfonate, 13.0203 g (0.05 mol) (methacryloxypropyl) methyldiethoxysilane and 13.2211 g (0.025 mol) of the hydrophobic monomer S2 prepared in Preparation Example 2 were added to 1000 mL of 1,4-dioxane, mixed and stirred, and the temperature was raised to 58° C.;

[0196] After nitrogen was passed through for 30 minutes, 2.35 g of azobis(N-hydroxyisobutylamidine) hydrate was added to the mixed solution, and the reaction was continued for 22 hours under stirring to obtain a crude product;

[0197] After adding 800 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P6).

[0198] Among them, the weight average molecular weight of the polymer is 2.96×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.33:0.18:0.05:0.025.

[0199] Example 7

[0200] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 42.3642 g (0.3 mol) of N, N-diethyl methacrylamide, 99.3875 g (0.25 mol) of sodium 2-acrylamido hexadecyl sulfonate, 7.0002 g (0.03 mol) (acrylamidopropyl) trimethoxysilane and 5.2884 g (0.01 mol) of the hydrophobic monomer S2 prepared in Preparation Example 2 were added to 1000 mL of N, N-dimethylformamide, mixed and stirred, and the temperature was raised to 44° C.;

[0201] After nitrogen was passed through for 30 min, 0.31 g of azobisisobutylimidazoline hydrochloride was added to the mixed solution, and the reaction was continued for 24 h under stirring to obtain a crude product;

[0202] After adding 800 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P7).

[0203] The weight average molecular weight of the polymer is 3.11×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.3:0.25:0.03:0.01.

[0204] Example 8

[0205] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 35.6879 g (0.36 mol) of N-vinyl-N-methylacetamide, 26.8857 g (0.17 mol) of sodium methyl propylene sulfonate, 28.5305 g (0.07 mol) (methacryloxypropyl) methyl diethoxyethoxymethoxysilane and 10.5769 g (0.02 mol) of the hydrophobic monomer S2 obtained in Preparation Example 2 were added to 760 mL of pyridine, mixed and stirred, and the temperature was raised to 57° C.;

[0206] After nitrogen was passed through for 30 minutes, 1.2 g of azodicarboxyethyl-2-isobutylamidine hydrate was added to the mixed solution, and the reaction was continued for 16 hours under stirring to obtain a crude product;

[0207] After adding 600 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P8).

[0208] The weight average molecular weight of the polymer is 2.86×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.36:0.17:0.07:0.02.

[0209] Example 9

[0210] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 33.948 g (0.3 mol) of N-isopropylacrylamide, 23.1311 g (0.1 mol) of 3-prop-2-enamidopropane-1-sulfonic acid potassium, 15.0638 g (0.08 mol) (acryloyloxyethyl) dimethylmethoxysilane and 3.8656 g (0.01 mol) of the hydrophobic monomer S3 obtained in Preparation Example 3 were added to 600 mL of N,N-dimethylacetamide, mixed and stirred, and the temperature was raised to 66°C;

[0211] After nitrogen was passed through for 30 min, 0.8 g of dimethyl azobisisobutyrate was added to the mixed solution, and the reaction was continued for 19.5 h under stirring to obtain a crude product;

[0212] After adding 500 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P9).

[0213] The weight average molecular weight of the polymer is 2.49×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.3:0.1:0.08:0.01.

[0214] Example 10

[0215] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 64.5795 g (0.5 mol) of N-(2-hydroxypropyl) acrylamide, 82.3741 g (0.25 mol) of potassium 2-acrylamidodecanesulfonate, 14.9297 g (0.03 mol) (acrylamidopropyl) triethoxyethoxymethoxysilane and 10.7525 g (0.03 mol) of the hydrophobic monomer S4 obtained in Preparation Example 4 were added to 1200 mL of N, N-dimethylacetamide, mixed and stirred, and the temperature was raised to 64°C;

[0216] After nitrogen was passed through for 30 min, 2 g of azobisisobutyronitrile was added to the mixed solution, and the reaction was continued for 21 h under stirring to obtain a crude product;

[0217] After adding 1000 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P10).

[0218] The weight average molecular weight of the polymer is 2.38×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.5:0.25:0.03:0.03.

[0219] Embodiment 11

[0220] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 34.5396 g (0.3 mol) of N-hydroxyethyl acrylamide, 24.5338 g (0.1 mol) of potassium 2-acrylamido-2-methylpropanesulfonate, 7.4505 g (0.03 mol) of γ-methacryloxypropyltrimethoxysilane and 8.4696 g (0.03 mol) of the hydrophobic monomer S5 obtained in Preparation Example 5 were added to 800 mL of tetrahydrofuran, mixed and stirred, and the temperature was raised to 56° C.;

[0221] After nitrogen was passed through for 30 minutes, 0.45 g of azobisisobutylamidine hydrochloride was added to the mixed solution, and the reaction was continued for 20 hours under stirring to obtain a crude product;

[0222] After adding 600 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P11).

[0223] The weight average molecular weight of the polymer is 3.05×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.3:0.1:0.03:0.03.

[0224] Example 12

[0225] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 43.4752 g (0.43 mol) of N-hydroxymethyl acrylamide, 46.0428 g (0.2 mol) of sodium 2-acryloyloxy-2-methylpropane sulfonate, 11.0168 g (0.04 mol) of N-(3-triethoxysilyl)propyl acrylamide and 4.2348 g (0.015 mol) of the hydrophobic monomer S5 obtained in Preparation Example 5 were added to 800 mL of N,N-dimethylformamide, mixed and stirred, and the temperature was raised to 88°C;

[0226] After nitrogen was passed through for 30 min, 0.6 g of azobiscyclohexylcarbonitrile was added to the mixed solution, and the reaction was continued for 17.5 h under stirring to obtain a crude product;

[0227] After adding 500 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P12).

[0228] The weight average molecular weight of the polymer is 2.18×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.43:0.2:0.04:0.015.

[0229] Embodiment 13

[0230] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 44.5155 g (0.35 mol) of N, N-diethylacrylamide, 51.2163 g (0.15 mol) of 2-acrylamido dodecyl sodium sulfonate, 9.3336 g (0.04 mol) (acrylamidopropyl) trimethoxysilane and 6.9298 g (0.02 mol) of the hydrophobic monomer S6 prepared in Preparation Example 6 were added to 960 mL of N, N-dimethylacetamide, mixed and stirred, and the temperature was raised to 86°C;

[0231] After nitrogen was passed through for 30 minutes, 1.12 g of azodimethyl N-2-hydroxybutyl acrylamide was added to the mixed solution, and the reaction was continued for 18 hours under stirring to obtain a crude product;

[0232] After adding 500 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P13).

[0233] The weight average molecular weight of the polymer is 2.77×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.35:0.15:0.04:0.02.

[0234] Embodiment 14

[0235] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 37.6705 g (0.38 mol) of N,N-dimethylacrylamide, 82.2366 g (0.23 mol) of potassium 2-acrylamidododecylsulfonate, 29.0255 g (0.05 mol) (methacryloxypropyl) triethoxymethoxysilane and 10.0158 g (0.02 mol) of the hydrophobic monomer S7 obtained in Preparation Example 7 were added to 1200 mL of N,N-dimethylacetamide, mixed and stirred, and the temperature was raised to 67°C;

[0236] After nitrogen was passed through for 30 min, 1.25 g of azobisisovaleronitrile was added to the mixed solution, and the reaction was continued for 20 h under stirring to obtain a crude product;

[0237] After adding 1000 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for 3 times. The product was extracted with a Soxhlet extractor using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant for 24 hours. The product was vacuum dried at 25°C to constant weight to obtain a polymer (denoted as P14).

[0238] The weight average molecular weight of the polymer is 2.84×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.38:0.23:0.05:0.02.

[0239] Embodiment 15

[0240] In a reactor equipped with a temperature control device, a reflux condenser and a constant pressure feeding device, 38.2977 g (0.38 mol) of methacrylamide, 49.2637 g (0.2 mol) of potassium 2-acryloyloxy-2-methylpropanesulfonate, 22.8305 g (0.06 mol) (methacryloyloxypropyl) triethoxymethoxysilane and 5.0079 g (0.01 mol) of the hydrophobic monomer S7 obtained in Preparation Example 7 were added to 1000 mL of 1,4-dioxane, mixed and stirred, and the temperature was raised to 61°C;

[0241] After nitrogen was passed through for 30 min, 0.57 g of azodiisopropylimidazoline was added to the mixed solution, and the reaction was continued for 21 h under stirring to obtain a crude product;

[0242] After adding 800 mL of anhydrous ethanol for precipitation, the product was filtered and washed with acetone for three times. The product was extracted with a Soxhlet extractor for 24 hours using a mixed solvent of glacial acetic acid and ethylene glycol in a volume ratio of 3:2 as an extractant. The product was vacuum dried at 25°C to constant weight to obtain a coating inhibitor (denoted as P15).

[0243] The weight average molecular weight of the polymer is 3.03×10 6 g / mol, and the molar ratio of structural unit A, structural unit B, structural unit C and structural unit D is 0.38:0.2:0.06:0.01.

[0244] Comparative Example 1:

[0245] The method of Example 1 was followed, except that the hydrophobic monomer S1 was not added, and other conditions were the same as Example 1, to obtain a polymer (denoted as D1).

[0246] Comparative Example 2:

[0247] The method of Example 1 was followed, except that the hydrophobic monomer S1 was replaced by the same molar amount of hexadecyl propyl ester, and other conditions were the same as in Example 1, to obtain a polymer (denoted as D2).

[0248] Comparative Example 3:

[0249] The method of Example 1 was followed, except that γ-methacryloxypropyltrimethoxysilane was not added, and other conditions were the same as Example 1, to obtain a polymer (denoted as D3).

[0250] Comparative Example 4:

[0251] The method of Example 1 was followed, except that γ-methacryloxypropyltrimethoxysilane was replaced with 5 times the molar amount of hexadecyldimethylallylammonium chloride, and other conditions were the same as Example 1, to obtain a polymer (denoted as D4).

[0252] Test Example 1: Suppression Performance Evaluation

[0253] (The test method comes from: "Research and Application of Strong Inhibition and Anti-collapse Drilling Fluid in Jinshan Gas Field" (Chu Qi, Li Tao, Zhang Tianxiao, et al., [J]. Science, Technology and Engineering, 2014, 14(22), 35-40.)

[0254] 40.0 g of shale 6-10 mesh cuttings were placed in high temperature aging tanks filled with clean water, 7% KCl (analytical grade), 0.6% KPAM (Q / SHCG 91-2016), 0.6% FA367 (SY / T 5696-2017), 0.3% polymers P1-P15 prepared in Examples 1-15 and polymers D1-D4 prepared in Comparative Examples 1-4, respectively, and rolled aged at 90°C, 120°C and 150°C for 16 h, then taken out, cooled to room temperature, and recovered through a 40-mesh sieve. The cuttings were dried at 105°C to constant weight, the cuttings were weighed, and the rolling recovery rate was calculated. The experimental results are shown in Table 1:

[0255] Table 1

[0256]

[0257] It can be seen from Table 1 that with the increase of aging temperature, the rolling recovery rate of cuttings decreased significantly. Compared with clean water, 7% KCl, 0.6% KPAM and 0.6% FA367, under the same aging temperature conditions, the rolling recovery rate of cuttings with 0.3% P1-P15 added was significantly higher, indicating that P1-P15 has a stronger ability to inhibit the hydration and dispersion of cuttings than conventional inhibitors. Compared with the rolling recovery rate of the rock cuttings added with P1, the rolling recovery rate of the rock cuttings added with D1-D2 is relatively low, indicating that the introduction of hydrophobic monomers containing phosphonate groups into the molecular chain of the sample helps to improve the ability of the sample to inhibit the hydration and dispersion of the rock cuttings under high temperature conditions, and its temperature resistance is also better than that of the sample with conventional hydrophobic monomers containing long alkyl chains introduced into the molecular chain; compared with the rolling recovery rate of the rock cuttings added with P1, the rolling recovery rate of the rock cuttings added with D3-D4 is relatively low, indicating that the introduction of siloxane groups into the molecular chain of the sample helps to improve the ability of the sample to inhibit the hydration and dispersion of the rock cuttings under high temperature conditions, and its temperature resistance is also better than that of the sample with quaternary ammonium groups introduced into the molecular chain.

[0258] Test Example 2: Weathering performance evaluation

[0259] 40.0 g of shale 6-10 mesh cuttings were placed in high-temperature aging tanks containing 0.3% coated inhibitor P1 prepared in Example 1 and coated inhibitors D1-D4 prepared in Comparative Examples 1-4, respectively, and were taken out after rolling aging at 120°C for 16h, 24h and 32h, respectively, and cooled to room temperature. The cuttings were recovered through a 40-mesh sieve, dried at 105°C to constant weight, the mass of the cuttings was weighed, and the rolling recovery rate was calculated. The experimental results are shown in Table 2.

[0260] Table 2

[0261]

[0262] As can be seen from Table 2, with the extension of aging time, the rolling recovery rate of the cuttings decreased significantly. Compared with the rolling recovery rate of the cuttings with P1 added, the rolling recovery rate of the cuttings with D1-D2 added is relatively low, indicating that the introduction of hydrophobic monomers containing phosphonate groups into the polymer chain of the sample helps to improve the weather resistance of the sample, and its weather resistance is also better than that of the sample with conventional hydrophobic monomers containing long alkyl chains introduced into the molecular chain; compared with the rolling recovery rate of the cuttings with P1 added, the rolling recovery rate of the cuttings with D3-D4 added is relatively low, indicating that the introduction of siloxane groups into the polymer chain of the sample helps to improve the weather resistance of the sample, and its weather resistance is also better than that of the sample with quaternary ammonium groups introduced into the molecular chain.

[0263] Test Example 3: Adsorption capacity test

[0264] Add 400mL of tap water to Example 1 and the corresponding raw materials, and Comparative Examples 3 and 4 in a high stirring cup, add 32g of clay at a certain stirring speed, and then add 1.6g of Na2CO3. Stir for 20 minutes, stop stirring at least twice during this period to scrape off the clay adhering to the container wall, and cure in a sealed container for 24 hours. After being divided into several equal parts, 0.3wt% of polymer P1 prepared in Example 1 and polymers D3 and D4 prepared in Comparative Examples 3 and 4 were added respectively. After stirring for 2 hours at a speed of 600r / min, let it stand for 2 hours, and use hot filtration method to determine the adsorption amount of different samples at different temperatures (the test method is from CN 105277675B). The experimental results show that the adsorption amount (mg / g) of the filter loss agent at different temperatures is shown in Table 3.

[0265] Table 3

[0266]

[0267] It can be seen from Table 3 that with the increase of temperature, the adsorption amount of the sample shows a significant downward trend. Under the same temperature conditions, the adsorption amount of P1 is significantly higher than that of D3 and D4, indicating that the introduction of siloxane groups into the polymer chain of the sample is beneficial to increase the adsorption amount of the sample, which plays a positive role in improving the coating inhibition effect of the sample under high temperature conditions.

[0268] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A hydrophobic monomer, characterized in that: The hydrophobic monomer has a structure shown in formula (1): Among them, R 10 and R 20 Each is independently selected from hydrogen or C1-C6 alkyl, R is selected from hydrogen, phenyl or C1-C6 alkyl, R 10 and R 20 Each independently selected from hydrogen, phenyl, C1-C 18 Alkyl or C6-C 18 Cycloalkyl, s is selected from a natural number of 0-9.

2. The hydrophobic monomer according to claim 1, characterized in that in, R 10 and R 20 Each is independently selected from C1-C4 alkyl, preferably selected from methyl, ethyl, isopropyl or isobutyl; Preferably, R is selected from phenyl or C1-C6 straight-chain alkyl, preferably selected from methyl, ethyl, n-butyl, n-hexyl or phenyl; Preferably, R 10 and R 20 Each independently selected from hydrogen, phenyl, C1-C 18 Straight-chain alkyl, preferably selected from hydrogen, methyl, n-propyl, n-pentyl, phenyl, n-decyl or n-heptadecayl; Preferably, s is selected from a natural number of 0-6, preferably selected from 1, 2 or 3.

3. The hydrophobic monomer according to claim 1 or 2, characterized in that The hydrophobic monomer is selected from the compounds shown in the following structural formula:

4. A method for preparing a hydrophobic monomer, characterized in that: The preparation method comprises: in the presence of a catalyst, subjecting a compound a represented by formula (2) and a compound b represented by formula (3) to a synthesis reaction to obtain the hydrophobic monomer; Among them, R 10 , R 20 ,R,s,R 10 , R 20 The same as the definition in any one of claims 1 to 3.

5. The preparation method according to claim 4, characterized in that: The catalyst is selected from at least one of low-valent titanium, low-valent tungsten, low-valent molybdenum, low-valent zirconium, low-valent vanadium and low-valent niobium; preferably low-valent titanium; Preferably, the method for preparing low-valent titanium comprises: dissolving a titanium-containing reagent and a reducing agent in a first solvent, and performing a reduction reaction to obtain the low-valent titanium; Preferably, the method for preparing low-valent titanium further comprises: the reduction reaction is carried out under a protective atmosphere, wherein the protective atmosphere is nitrogen and / or argon; Preferably, the first solvent is selected from tetrahydrofuran and / or dimethyl ether; Preferably, the titanium-containing reagent is selected from at least one of titanium trichloride, titanium tetrachloride and titanium powder; the reducing agent is selected from at least one of K, Li, Na, Zn+CuCl, LiAlH4, Mg, Mg+Hg, Li+Hg and chlorosilane; Preferably, the titanium-containing reagent is titanium tetrachloride; the reducing agent is Zn and CuCl; Preferably, the concentration of titanium tetrachloride in the first solvent is 0.3-0.6 mmol / mL, the concentration of Zn in the first solvent is 0.2-0.6 mmol / mL, and the concentration of CuCl in the first solvent is 0.03-0.05 mmol / mL.

6. The preparation method according to claim 5, characterized in that: Before the reaction of compound a and compound b, compound a and compound b are dissolved in a second solvent; Preferably, the volume ratio of the first solvent to the second solvent is 2-4:1; Preferably, the molar ratio of compound a to compound b is 1:1.2-1.8; Preferably, the temperature of the synthesis reaction is -10°C to 0°C or 68-75°C; Preferably, the synthesis reaction time is 2-8 h, preferably 3-6 h.

7. A hydrophobic monomer obtained by the preparation method according to any one of claims 4 to 6.

8. A polymer, characterized in that The polymer contains a structural unit A derived from a monomer a represented by formula (4), a structural unit B derived from a monomer b represented by formula (5), and a structural unit C and a structural unit D derived from a monomer c represented by formula (6); Wherein, the structural unit D is derived from the hydrophobic monomer according to any one of claims 1 to 4 and 7; Among them, in formula (4), R 1 is selected from hydrogen or C1-C6 alkyl, R 2 Selected from Among them, R a and R b Each is independently selected from hydrogen, C1-C6 alkyl, C1-C6 alkyl alcohol or C1-C8 alkyl ketone, R c is selected from hydrogen or C1-C6 alkyl, R d Selected from methyl, ethyl, or Among them, in formula (5), R 3 Selected from H or C1-C6 alkyl, R 4 Selected from wherein j, k, and l are each independently selected from a natural number of 0 to 3, m and n are each independently selected from an integer of 4 to 14, and A is selected from H, Na, K, Rb or Cs, preferably selected from H, Na or K; Among them, in formula (6), R 5 Selected from H or C1-C6 alkyl, R 6 is a siloxane group selected from wherein p and q are each independently selected from a natural number of 0-6, preferably a natural number of 0-3, more preferably 1, 2 and 3, R a , R b , R c , R d , R e and R f Each is independently selected from an alkyl group or an -OR' group, wherein the alkyl group is selected from a methyl group, R' is selected from a methyl group, an ethyl group, -CH2CH2OCH3 or -CH2CH2OCH2CH2OCH3, and R a , R b and R c Not all methyl groups, R d , R e and R f At least one of them is an alkoxy group.

9. The polymer according to claim 8, characterized in that The molar ratio of the structural unit A, the structural unit B, the structural unit C and the structural unit D is (30-50): (10-25): (3-8): (1-3).

10. The polymer according to claim 8 or 9, characterized in that in, The weight average molecular weight of the polymer is 2.15×10 6 -3.25×10 6 g / mol.

11. The polymer according to any one of claims 8 to 10, characterized in that The polymer comprises at least one of the following polymers: Polymer-1, the structural unit A is derived from acrylamide, the structural unit B is derived from sodium p-styrene sulfonate, the structural unit C is derived from γ-methacryloxypropyltrimethoxysilane, and the structural unit D is derived from a compound of formula (1-1), Polymer-2, the structural unit A is derived from diacetone acrylamide, the structural unit B is derived from sodium p-allyl sulfonate, the structural unit C is derived from N-(3-triethoxysilyl)propyl acrylamide, and the structural unit D is derived from a compound of formula (1-1), Polymer-3, the structural unit A is derived from N-vinylacetamide, the structural unit B is derived from sodium 2-acryloyloxyhexadecyl sulfonate, the structural unit C is derived from (methacryloyloxymethyl)methyldimethoxysilane, and the structural unit D is derived from a compound of formula (1-1), Polymer-4, the structural unit A is derived from N-ethylacrylamide, the structural unit B is derived from 3-prop-2-enoyloxypropane-1-sulfonic acid, the structural unit C is derived from (methacryloxypropyl) dimethylethoxyethoxymethoxysilane, and the structural unit D is derived from a compound of formula (1-1), Polymer-5, the structural unit A is derived from N,N-bis(2-hydroxyethyl)methacrylamide, the structural unit B is derived from 2-acrylamide-2-methylpropanesulfonic acid, the structural unit C is derived from (methacryloxypropyl)triethoxymethoxysilane, and the structural unit D is derived from a compound of formula (1-2), Polymer-6, the structural unit A is derived from N-(2-hydroxypropyl)acrylamide, the structural unit B is derived from sodium 2-acrylamidooctane sulfonate, the structural unit C is derived from (methacryloxypropyl)methyldiethoxysilane, and the structural unit D is derived from a compound of formula (1-2), Polymer-7, the structural unit A is derived from N,N-diethyl methacrylamide, the structural unit B is derived from 2-acrylamido hexadecyl sodium sulfonate, the structural unit C is derived from (acrylamidopropyl) trimethoxysilane, and the structural unit D is derived from a compound of formula (1-2), Polymer-8, the structural unit A is derived from N-vinyl-N-methylacetamide, the structural unit B is derived from sodium methyl propylene sulfonate, the structural unit C is derived from (methacryloxypropyl)methyldiethoxyethoxymethoxysilane, and the structural unit D is derived from a compound of formula (1-2), Polymer-9, the structural unit A is derived from N-isopropylacrylamide, the structural unit B is derived from potassium 3-prop-2-enamidopropane-1-sulfonate, the structural unit C is derived from (acryloyloxyethyl)dimethylmethoxysilane, and the structural unit D is derived from a compound of formula (1-3), Polymer-10, the structural unit A is derived from N-(2-hydroxypropyl)acrylamide, the structural unit B is derived from potassium 2-acrylamidodecylsulfonate, the structural unit C is derived from (acrylamidopropyl)triethoxyethoxymethoxysilane, and the structural unit D is derived from a compound of formula (1-4), Polymer-11, the structural unit A is derived from N-hydroxyethyl acrylamide, the structural unit B is derived from potassium 2-acrylamido-2-methylpropanesulfonate, the structural unit C is derived from γ-methacryloxypropyltrimethoxysilane, and the structural unit D is derived from a compound of formula (1-5), Polymer-12, the structural unit A is derived from N-hydroxymethyl acrylamide, the structural unit B is derived from sodium 2-acryloyloxy-2-methylpropane sulfonate, the structural unit C is derived from N-(3-triethoxysilyl)propyl acrylamide, and the structural unit D is derived from a compound of formula (1-5), Polymer-13, the structural unit A is derived from N,N-diethylacrylamide, the structural unit B is derived from 2-acrylamido dodecyl sodium sulfonate, the structural unit C is derived from (acrylamidopropyl)trimethoxysilane, and the structural unit D is derived from a compound of formula (1-6), Polymer-14, the structural unit A is derived from N,N-dimethylacrylamide, the structural unit B is derived from potassium 2-acrylamidododecylsulfonate, the structural unit C is derived from (methacryloxypropyl)triethoxymethoxysilane, and the structural unit D is derived from a compound of formula (1-7), Polymer-15, the structural unit A is derived from methacrylamide, the structural unit B is derived from potassium 2-acryloyloxy-2-methylpropanesulfonate, the structural unit C is derived from (methacryloyloxypropyl)triethoxymethoxysilane, and the structural unit D is derived from a compound of formula (1-7), 12. A method for preparing a polymer, characterized in that: The method comprises: in the presence of an initiator, polymerizing monomer a, monomer b, monomer c and the hydrophobic monomer described in any one of claims 1 to 4 and 7 to obtain the polymer.

13. The method according to claim 12, characterized in that The initiator is selected from one or more of an azo initiator, an organic peroxide initiator, an inorganic peroxide initiator, and an oil-soluble redox initiator, preferably an azo initiator; Preferably, the azo initiator is selected from one or more of azobisisobutylimidazoline hydrochloride, azoisobutylcyanoformamide, azobisisobutyronitrile, azobiscarboxyethyl-2-isobutylamidine hydrate, azodimethyl N-2-hydroxybutylacrylamide, azobiscyclohexylcarbonitrile, azobisisovaleronitrile, azobisisoheptylnitrile, azobiscyanovaleric acid, azobisisobutylamidine hydrochloride, azobisisopropylimidazoline, azobisN-hydroxyisobutylamidine hydrate, azobisN,N'-cyclobutylisobutylamidine hydrate, azobisdimethylisobutyrate, and 2,2'-azobis(N-cyclohexylisobutylamidine) hydrochloride.

14. The method according to claim 12 or 13, characterized in that The polymerization reaction temperature is 40-105°C, preferably 44-104°C; the polymerization reaction time is 16-24h; Preferably, the molar ratio of the monomer a, monomer b, monomer c and the hydrophobic monomer is (30-50): (10-25): (3-8): (1-3); Preferably, the added amount of the initiator is 0.2-2 wt % of the total weight of the monomer a, the monomer b, the monomer c and the hydrophobic monomer.

15. A polymer obtained by the preparation method according to any one of claims 12 to 14.

16. Use of the polymer according to any one of claims 8 to 11 and 15 as a coated inhibitor in drilling fluid.

Citation Information

Patent Citations

  • Turnover device for automatic detection of glass

    CN105277675A

  • A modified starch-coated anti-collapse agent for drilling fluid and its preparation method

    CN109971438B

Cited By

  • Filtrate reducer as well as preparation method and application thereof

    CN120682414A